Thermodynamic analysis of plasma gasification of agricultural waste - Messerle, V.Е.; Ustimenko, А.B.; Slavinskaya, N.А.; Sitdikov, Zh. (Recent Contributions to Physics, 2019)
Most of the agricultural waste (AW) comes from poultry farms and livestock farms mainly in the form of bird droppings and cattle dung. Irrational use of large volumes of such waste negatively affects the environment. Modern technologies allow utilizing agricultural waste to produce energy gas. Plasma recycling of waste from the agro-industrial complex allows intensifying the process of obtaining energy gas consisting mainly of synthesis gas (СО+Н2) and a 150–200-fold increase in the gas productivity of the plasma gasifier compared with biogas generators. This article is devoted to the thermodynamic modelling of AW plasma-processing. The thermodynamic analysis of the waste plasma processing was performed using the universal program of thermodynamic calculations TERRA. In the work under the AW means the excrement of farm animals (manure). For research, dried mixed manure (dung with 30% moisture content) from cattle is used. Thermodynamic calculations showed that during plasma gasification and pyrolysis of AW, high-calorie combustible gas is produced with a synthesis gas yield of 65.2 and 68.5%, respectively. No harmful components were detected. Plasma gasifier will allow to effectively process various types of AW into high calorific energy gas, consisting mainly of synthesis gas, and into neutral slag. The technological scheme of AW plasma processing has been developed. Using proposed plasma plant that implements this scheme, depending on the composition of the AW, up to 1.7 m3 of dry energy gas can be obtained from 1 kg of AW. At the same time, its caloric content will vary from 8500 to 300 MJ/Nm3. The composition of the energy gas will be following, vol.%: H2 - 35-39, CO - 29-31, CO2 - 4-6, N2 - 10-14, H2O - 13-18. Such gas can be used as a working medium of highly efficient electric generators of a new generation, including solid oxide fuel cells or as a raw material for the production of synthetic motor fuels (methanol, dimethylether)